Simultaneous removal of hydrocarbons and sulfate from groundwater using a "bioelectric well". (20th August 2021) - Tucci, Matteo; Carolina, Cruz Viggi; Resitano, Marco; Matturro, Bruna; Crognale, Simona; Pietrini, Ilaria; Rossetti, Simona; Harnisch, Falk; Aulenta, Federico
Highlights: A bioelectrochemical reactor for bioremediation of "real groundwater". Hydrocarbons (toluene and PH) and sulfate were simultaneously removed. An apparent sulfur cycle diminished the sulfate reduction performance. Abstract: Petroleum hydrocarbons (PHs) are often found in groundwater due to human activities like accidental spills, causing health and environmental risks, and requiring remediation. Microbial Electrochemical Technologies (METs) have emerged as a promising alternative to conventional bioremediation techniques for the treatment of PH-contaminated groundwater. However, the field-application of these promising sustainable as well as cost-effective technologies is still scarce. One major reason is the lack of scalable reactor configurations. Herein, an upgraded version of the "bioelectric well", a novel tubular bioelectrochemical reactor that can be installed directly within a groundwater well, was tested for the simultaneous removal of oxidableoxidizable (i.e., toluene and other PH) and reducible (i.e., sulfate) compounds from a real contaminated groundwater. After a proof-of-concept study in batch mode, the system was operated in continuous-flow mode for 48 days with the anode polarized at 0.2 V vs. SHE and a hydraulic retention time of 11 h. In these conditions, a steady-state removal rate of toluene as high as 31 ± 2 mg L −1 d −1 was achieved, which was more than double the value observed with the open circuit potential (OCP) control and one of the highest reported in literature. The electrode polarization went along with a higher abundance of key-functional genes involved in toluene degradation. This was not only showing its clear functional connection to the microbial metabolism, but further allowed to identify the involved electrogenic biodegradation pathway. In addition, the system simultaneously removed sulfate (30 ± 1 mg L −1 d −1 ), with bacteria likely using the H2 generated at the cathode as electron donor. Nevertheless, the apparent sulfate removal rate in the polarized and in the OCP runs was similar. The analysis of the microbial communities evidenced a high abundance of the genus Chlorobium in the effluent of the polarized run. These microorganisms were probably responsible for the continuous oxidative regeneration of sulfate from the sulfide produced at the cathode by sulfate-reducing bacteria. This phenomenon probably hindered the overall removal of sulfate by the bioelectrochemical system. Graphical abstract: Image, graphical abstract